2016
DOI: 10.1021/acsnano.6b02484
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Description of Raman Scattering from Molecules in Plasmonic Cavities

Abstract: Plasmon-enhanced Raman scattering can push single-molecule vibrational spectroscopy beyond a regime addressable by classical electrodynamics. We employ a quantum electrodynamics (QED) description of the coherent interaction of plasmons and molecular vibrations that reveal the emergence of nonlinearities in the inelastic response of the system. For realistic situations, we predict the onset of phonon-stimulated Raman scattering and a counterintuitive dependence of the anti-Stokes emission on the frequency of ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
271
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 167 publications
(281 citation statements)
references
References 83 publications
(191 reference statements)
7
271
0
3
Order By: Relevance
“…Analogous optomechanical systems use macroscopic vibrational modes such as cantilevers [9,10], beams [11], or pillars [12][13][14][15] coupled to highfinesse optical cavities in order to demonstrate a variety of effects such as cooling to the quantum vibrational ground state [16], parametric oscillation [17], and supercontinuum comb generation [18]. Recent theory [19,20] and experiments [8,21] have shown that this same optomechanical Hamiltonian describes vibrating molecular bonds in nanocavities, but with single-photon coupling coefficients ℏg 0 ∼ 10-100 meV, a millionfold larger than for macroscopic resonators. Here, we explore how this coupling can be used to elicit stimulated phonon scattering within vibrating bonds, leading toward phonon lasing or "phasing," observed previously in microfabricated mechanical oscillators [22][23][24], and we suggest how such mechanical resonances can lead to chemical reactions [ Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analogous optomechanical systems use macroscopic vibrational modes such as cantilevers [9,10], beams [11], or pillars [12][13][14][15] coupled to highfinesse optical cavities in order to demonstrate a variety of effects such as cooling to the quantum vibrational ground state [16], parametric oscillation [17], and supercontinuum comb generation [18]. Recent theory [19,20] and experiments [8,21] have shown that this same optomechanical Hamiltonian describes vibrating molecular bonds in nanocavities, but with single-photon coupling coefficients ℏg 0 ∼ 10-100 meV, a millionfold larger than for macroscopic resonators. Here, we explore how this coupling can be used to elicit stimulated phonon scattering within vibrating bonds, leading toward phonon lasing or "phasing," observed previously in microfabricated mechanical oscillators [22][23][24], and we suggest how such mechanical resonances can lead to chemical reactions [ Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Using an optomechanical model, it is possible to extract the photon-phonon coupling [8,20]. When the nanocavities are formed by ultrathin gaps between plasmonic metal nanostructures that trap the optical field, this strongly amplified process is termed surface-enhanced Raman spectroscopy (SERS) of the molecules in the gap.…”
Section: Introductionmentioning
confidence: 99%
“…a molecule. Such plasmonic cavities are as well of experimental [6][7][8] as of theoretical interest [9].…”
Section: Introductionmentioning
confidence: 99%
“…This process is dramatically amplified by the extreme confinement of the incident light in the plasmonic gap. As a result, the population of excited vibrational states (at frequencies ) is boosted above that provided by thermal excitations from the environment at temperature , , by an additional contribution due to the optomechanical coupling of the plasmonic cavity with the molecular vibration (9). We first model the interaction of quantized plasmons with phonons in the classical limit of weak coupling between the vibrations and cavity plasmons (with for cavity decay rate ), through the optomechanical Hamiltonian described in (7,9).…”
mentioning
confidence: 99%
“…As a result, the population of excited vibrational states (at frequencies ) is boosted above that provided by thermal excitations from the environment at temperature , , by an additional contribution due to the optomechanical coupling of the plasmonic cavity with the molecular vibration (9). We first model the interaction of quantized plasmons with phonons in the classical limit of weak coupling between the vibrations and cavity plasmons (with for cavity decay rate ), through the optomechanical Hamiltonian described in (7,9). This gives (1) with volume-dependent optomechanical amplification rate dependent on optomechanical coupling strength and laser power , with phonon decay rate (full expressions in (7), Section S1 and (9)).…”
mentioning
confidence: 99%